A importância do comércio internacional para o desenvolvimento no Estado do Maranhão: análise dos anos 2010 a 2020 - FREIRE NETO, Raimundo Plácido (2022)
The topics covered, international trade and development, are relevant issues for international relations. In view of the importance of development, we will approach this concept, making a historical contribution from the thinking of authors such as Adam Smith and David Ricardo, as well as contemporary authors such as Amartya Sen and Celso Furtado, in order to demonstrate that income is an important factor for development, however, it is not the means to an end. Furthermore, we also intend to show the importance of international trade for the development of countries, especially developing countries (DCs) and least developed countries (LDCs), which have difficulties in implementing and participating in the multilateral trading system. The aim of this dissertation is to analyze the impacts of international trade on the development of Maranhão and specify why the state has the lowest Human Development Indexes (HDI), even concentrating wealth and significant trade, considering that Maranhão has actively participated in the international market since colonial Brazil. Based on research and the need to analyze social, legal and economic aspects, we approach how international trade can actually interfere in the development of the population of Maranhão.